Exploring the Influence of Power in the Dynamics of Customer-Supplier Coopetition in the Case of Supplier Dominance - Tréhan, Natacha; Pourrat, Cyril (Management international / International Management / Gestiòn Internacional, 2019)
Coopetition combines paradoxical forces: competition and cooperation. Many previous works have examined the forces driving competitors to cooperate. Little research investigates the factors driving competition, in particular the influence of power in the case of client-supplier coopetition. To fill this gap, a longitudinal case study is being conducted in the telecom sector. It concerns the coopetition between the French operator Orange and Apple its device supplier. The study shows that supplier dominance combined with low trust fosters competition in customer-supplier coopetition.